Příspěvek k poznání vodních měkkýšů nivy Ploučnice mezi Českou Lípou a Mimoní - Luboš Beran (Malacologica Bohemoslovaca, 2016)
This paper presents results of a malacological survey of the Ploučnice River and its floodplain between the town of Česká Lípa and Mimoň in Northern Bohemia. Thirty nine species of aquatic molluscs (23 gastropods and 16 bivalves) were found at 64 sites during the research realised between years 2000 and 2016. Twenty three species were identified in the Ploučnice River, thirteen species in its tributaries and thirty three molluscs inhabited different aquatic habitats in the floodplain. The occurrence of rare bivalve Pisidium amnicum and P. tenuilineatum populations was recorded. The presence of any non-native species was documented.